PENGEMBANGAN MEDIA EVALUASI BERBASIS APLIKASI EXCEL TO WHATSAPP - Firza Agung Prakoso; Rochmawati Rochmawati (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
The research aims to 1) develop an e-learning evaluation media based on the Excel to WhatsApp application. 2) Testing the feasibility of evaluation media developed by experts. 3) Testing the feasibility of the media based on the responses of class X students in basic banking subjects at SMK N 1 Probolinggo. This development refers to the 4D model by Thiagarajan which includes the stages of define, design, develop, and disseminate. The results of the review and expert validation in this study indicate that the feasibility of the media, the feasibility of evaluation, and the feasibility of the material get an average of 88% with the criteria of